Optimization of Lignin Conversion by Hydrothermal Method for Recovery of Vanillin - Sriprom, Pongsert; Leephisuth, Pornyamon; Neramittagapong, Arthit; Neramittagapong, Sutasinee (My University, 2020)
This work aimed to optimize lignin conversion to vanillin by hydrothermal method. An experiment was designed by Box-Benhken Design (BBD). Temperature, NaOH concentration, and reaction time were chosen as independent parameters for achieving the optimum reaction condition. The reaction products were analyzed by high-performance liquid chromatography. Based on the experimental results, the optimum condition for the hydrothermal process was predicted using the response surface method. The maximum vanillin production of 18.1 mg/L was predicted at the optimum condition given by the temperature of 142 °C, NaOH concentration of 9.2 g/L, and reaction time of 32 min. The conversion of lignin to vanillin was experimented using the predicted optimal condition to verify the prediction. It was found that the hydrothermal method at the optimum condition yielded 18.1 ± 2 mg/L of vanillin, which was in good agreement with the predicted value. It was also found that the yield of vanillin was influenced by temperature, NaOH concentration, and the interaction of both parameters, whereas the reaction time was much less influential.
Keywords: Hydrothermal; Lignin conversion; Vanillin